2015
DOI: 10.1210/jc.2014-2280
|View full text |Cite
|
Sign up to set email alerts
|

miR-142–3p Down-Regulation Contributes to Thyroid Follicular Tumorigenesis by Targeting ASH1L and MLL1

Abstract: These data demonstrate that miR-142-3p downregulation has a role in thyroid tumorigenesis, by regulating ASH1L and MLL1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 38 publications
2
43
0
Order By: Relevance
“…Similar results were observed for miR-142-3p that also seems to play a tumor-suppressive role in the thyroid gland. Its downregulation in tumor was associated with the aberrant action of Trithorax group proteins, major regulators of the homeobox gene expression (77). Another study revealed an important role of miR-122 significantly upregulated in FTC compared with FA.…”
Section: The Potential Of Micrornas In Thyroid Cancer Treatmentmentioning
confidence: 96%
“…Similar results were observed for miR-142-3p that also seems to play a tumor-suppressive role in the thyroid gland. Its downregulation in tumor was associated with the aberrant action of Trithorax group proteins, major regulators of the homeobox gene expression (77). Another study revealed an important role of miR-122 significantly upregulated in FTC compared with FA.…”
Section: The Potential Of Micrornas In Thyroid Cancer Treatmentmentioning
confidence: 96%
“…In addition to its role in leukemia, ASH1L is overexpressed in a variety of solid tumors, including thyroid and breast cancer [87,88]. In thyroid cancer, ASH1L is overexpressed in tumor-specific truncated forms, although what parts of the protein are truncated or what processing events produce them has not been explored.…”
Section: Ash1l: Hox Gene Activator With Emerging Role In Cancermentioning
confidence: 99%
“…In thyroid cancer, ASH1L is overexpressed in tumor-specific truncated forms, although what parts of the protein are truncated or what processing events produce them has not been explored. Expression of the miRNA miR-142-3p suppresses ASH1L protein expression by binding to the ASH1L 3´UTR, an effect correlated with inhibition of colony formation and slowing of thyroid cancer cell growth [87]. Interestingly, in mouse embryonic stem cells ASH1L is regulated by a different miRNA, miR-290, which downregulates ASH1L expression and prevents aberrant overexpression of Hoxa, Hoxb, Hoxc and Hoxd genes [89].…”
Section: Ash1l: Hox Gene Activator With Emerging Role In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…miR-142-3p has been reported to be downregulated in diverse types of cancer, including leukemia, thyroid follicular carcinomas, cervical cancer, hepatic cancer, glioblastoma, osteosarcoma and non-small cell lung cancer (16)(17)(18)(19)(20)(21)(22). miR-142-3p has been demonstrated to contribute to carcinogenesis by regulating cell cycle, cell migration, apoptosis and invasion by targeting various signaling pathways and…”
Section: Introductionmentioning
confidence: 99%